Comparative Analysis of Peatland Oil Palm Farmers' Satisfaction Level with the Service Performance of Fresh Fruit Bunch Marketing Institutions in XIV Koto District, Mukomuko Regency - Danda Ifki Prayata; Ellys Yuliarti; Ridha Rizki Novanda; Nur Qomariah Hayati (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2025)
The research was conducted in XIV Koto District, focusing mainly on peatland oil palm farmers' satisfaction with the performance of fresh fruit bunch marketing institutions. The objectives of this study were to analyze the level of satisfaction of peatland oil palm farmers with service performance attributes and to analyze differences in farmers' satisfaction with the service performance of marketing institutions in XIV Koto District. Samples were taken using the census method with a total sample size of 98 farmers. Analysis of farmer satisfaction levels using Importance Performance Analysis and Customer Satisfaction Index methods—comparative analysis using One Way Anova test. The results showed that farmers were satisfied overall with the performance of village collectors and large traders, while the performance of services at the factory was considered very satisfactory. In the comparative analysis, a significance value of 0.291 was obtained, which means that there is no significant difference in the level of satisfaction of peatland oil palm farmers with the service performance of village collectors, large traders, and factories in XIV Koto District, Mukomuko Regency. The results of this study are expected to be evaluation material for marketing institutions in improving service performance for peatland oil palm farmers.